Crecimiento económico, desempleo e inflación: Un estudio econométrico con series de tiempo para Ecuador, período 1991-2020 - Naranjo Coronel, Ana Cecibel (2023)
In 2020 the unemployment rate at the national level had an increase of 1.12 percentage points, reaching 4.96% of the economically active population (EAP), comparing December 2019 and December 2020. Unemployment remains a structural problem of the Ecuadorian economy that has not been solved either before or after dollarization. This research uses time series cointegration techniques with the objective of determining whether economic growth and inflation explain unemployment in Ecuador, period 1991 and 2020, through time series, with the purpose of proposing policies to reduce unemployment levels. The results show that there is a positive relationship in the two models. That is, with an increase in GDP, the unemployment rate tends to increase; and with an increase in unemployment, inflation is not reduced, on the contrary. As for Granger causality, in the first model there is a unidirectional relationship between taxes, which is the first control variable, and unemployment, while in the second model there is bidirectional causality from taxes and inflation to unemployment, except between foreign direct investment, which is the second control variable, and unemployment. As recommendations, it is proposed to apply fiscal policy tools, exhaustive price control, strengthening of an industrial strategy transforming growth into employment, to generate the necessary conditions where unemployment is progressively reduced to avoid a labor and economic deficit.